The Changing Global Order
XXVII, 456 p. 14 illus., 7 illus. in color.
Keywords: This volume offers a comprehensive evaluation of the concept of global order, with a particular emphasis on the role of regional organisations within global governance institutions such as the United Nations. Building from a solid theoretical base it draws upon the expertise of numerous leading international scholars offering a broad array of timely and relevant case studies. These all take into consideration the historical setting, before analysing the contemporary situation and offering suggestions for potential realignments and readjustments that may be witnessed in the future. The volume adopts an interdisciplinary approach when addressing some of the most pressing issues of global governance which our global community must tackle. This presents the readers an opportunity to understand related topics such as political economy, international law, institutions of global governance, in conjunction with the academic field of International Relations (IR). It further helps studentsand interested readers understand the theoretical and practical foundations to the changing nature of global affairs. .